Chronic renal failure; an important feature of the Laurence-Moon-Biedl syndrome. Issue 752 (June 1988) - Williams, B.; Jenkins, D.; Walls, J.
Abstract : Two cases of end stage renal failure occurring in association with the Laurence-Moon-Biedl syndrome are reported. Abnormalities in renal function and morphology are increasingly recognized in these patients in whom uraemia is an important cause of morbidity and early mortality. The presence of renal impairment, occurring as frequently as any of the pentad of features that characterize the syndrome, has important implications for the prognosis and long term management of these patients.